TERAPI MUSIK UNTUK MENURUNKAN KECEMASAN PASIEN INTRA OPERASI SECTIO CAESAREA DI RS KRISTEN NGESTI WALUYO TEMANGGUNG: CASE REPORT - Setyoraharjo, Tuhu; Melati, Nimsi; Sudarto, Sudarto (Forind Press, 2025)
Cesarean section procedures performed under spinal anesthesia allow patients to remain conscious during surgery; however, they often induce anxiety due to the stressful environment of the operating room. If not properly managed, anxiety can negatively impact the patient’s physiological stability and interfere with the smooth execution of the surgical procedure. Music therapy is a non-pharmacological approach that has been proven to be safe, comfortable, and effective in reducing anxiety levels. This study utilized a case report method, implementing a 60-minute music therapy intervention delivered through earphones during the surgical process. Observational results indicated a significant decrease in the patient’s anxiety level, as measured by the State-Trait Anxiety Inventory score, which dropped from 55 (moderate anxiety) to 31 (mild anxiety). Additionally, the patient’s heart rate decreased from 102 bpm to 92 bpm, and blood pressure from 130/84 mmHg to 120/88 mmHg, while the respiratory rate remained stable at 20 breaths per minute. These findings suggest that music therapy is effective in reducing anxiety in patients undergoing cesarean section with spinal anesthesia.